9514 1404 393
Answer:
cuberoot(a) - 1/tenthroot(a)
Explanation:
The applicable rule of exponents seems to be ...
(a^b)^c = a^(bc)
a^-b = 1/a^b
__
Expressing all radicals using rational exponents, we want to simplify ...
![a^{(1)/(3)}-(a^{(2)/(5)})(a^{-(1)/(2)})\\\\=a^{(1)/(3)}-a^{(4-5)/(10)}\\\\=a^{(1)/(3)}-a^{-(1)/(10)}=\boxed{\sqrt[3]{a}-\frac{1}{\sqrt[10]{a}}}\\\\=\boxed{\sqrt[3]{a}-\frac{\sqrt[10]{a^9}}{a}}](https://img.qammunity.org/2022/formulas/mathematics/college/seeo7ywebaxcbuwqt25b7fuihj5nmf4swg.png)
__
We have shown two simplified expressions. You can choose the one that matches your requirements. Sometimes we don't want any radicals in the denominator.